Phytoseiidae Database: a website for taxonomic and distributional information on phytoseiid mites (Acari) - Demite, Peterson R.; Mcmurtry, James A.; de Moraes, Gilberto J. (Zootaxa, 2014)
This paper announces a database on the taxonomy and distribution of mites of the family Phytoseiidae Berlese, which is available online at http://www.lea.esalq.usp.br/phytoseiidae/. Synthesis of species diversity per genus, subfamily and country are given. Information about use of the database is provided.